3p-4m-7=

Simple and best practice solution for 3p-4m-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p-4m-7= equation:


Simplifying
3p + -4m + -7 = 0

Reorder the terms:
-7 + -4m + 3p = 0

Solving
-7 + -4m + 3p = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + -4m + 7 + 3p = 0 + 7

Reorder the terms:
-7 + 7 + -4m + 3p = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -4m + 3p = 0 + 7
-4m + 3p = 0 + 7

Combine like terms: 0 + 7 = 7
-4m + 3p = 7

Add '-3p' to each side of the equation.
-4m + 3p + -3p = 7 + -3p

Combine like terms: 3p + -3p = 0
-4m + 0 = 7 + -3p
-4m = 7 + -3p

Divide each side by '-4'.
m = -1.75 + 0.75p

Simplifying
m = -1.75 + 0.75p

See similar equations:

| 3r-8s=-25 | | 7(40-x)=245 | | 5p+6=3p-8 | | 12-3=-13 | | 8y+11=3y+29 | | 9e-7=7-11 | | 9t-4a-4= | | f(y)=(4y^2/3-6y^4/3)^2 | | 1464÷3/4 | | 2/5n=3/20 | | (14+2x)(26+2x)=589 | | Nx2/5=3/20 | | Nx2/3=3/20 | | 5y-3a+6= | | N(2/3)=3/20 | | f(y)=(7-3y^3)3 | | 70-y-y=54 | | 4*v=16 | | f(x)=(8x^2+7) | | W=4w-56 | | 6+.5y=-2(3-.25y) | | f(x)=(x+5) | | an=(1/2)n | | .08*1155= | | c(x)=x+100 | | -4x=5x-18 | | x+109=1396.6+-1229.6 | | 17+7g=6g | | 5(10-y)= | | 8-17t=-16t-12 | | an=2-1/3n | | 10-10x=0 |

Equations solver categories